The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1210/en.139.4.1738
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of Region-Specific Sex Differences in Androgen Receptor Messenger Ribonucleic Acid Expression in the Rat Forebrain

Abstract: Testosterone and its metabolites are the principal gonadal hormones responsible for sexual differentiation of the brain. However, the relative roles of the androgen receptor (AR) vs. the estrogen receptor in specific aspects of this process remain unclear due to the intracellular metabolism of testosterone to active androgenic and estrogenic compounds. In this study, we used an 35S-labeled riboprobe and in situ hybridization to analyze steady state, relative levels of AR messenger RNA (mRNA) expression in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
59
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(71 citation statements)
references
References 0 publications
12
59
0
Order By: Relevance
“…All of these data, taken together, indicate that various AR antibodies reveal a similar AR-ir in the brain of each species. It should be noted that the immunohistochemical distribution of AR, as indicated by the present study, in general, agrees well with that revealed by autoradiography in the rat and monkey brain (with tritiated testosterone or tritiated dihydrotestosterone; Clancy et al, 1992), with in situ hybridization studies in the rat brain (Simerly et al, 1990;McAbee et al, 1998), and with PG21 staining results in the Syrian hamster brain (Wood and Newman, 1999), the ferret brain (Kashon et al, 1996), and the monkey brain (Wu et al, 1995).…”
Section: Ar Distribution Compared With Different Speciessupporting
confidence: 90%
“…All of these data, taken together, indicate that various AR antibodies reveal a similar AR-ir in the brain of each species. It should be noted that the immunohistochemical distribution of AR, as indicated by the present study, in general, agrees well with that revealed by autoradiography in the rat and monkey brain (with tritiated testosterone or tritiated dihydrotestosterone; Clancy et al, 1992), with in situ hybridization studies in the rat brain (Simerly et al, 1990;McAbee et al, 1998), and with PG21 staining results in the Syrian hamster brain (Wood and Newman, 1999), the ferret brain (Kashon et al, 1996), and the monkey brain (Wu et al, 1995).…”
Section: Ar Distribution Compared With Different Speciessupporting
confidence: 90%
“…Similar findings have been reported in rats [60,61]. By contrast, sex differences in AR immunoreactivity favor males, with increased levels of AR mRNA and protein in MPOA and BST of male sheep [62], hamsters [63], rats [64], and mice [65]. Similar sex differences in AR were not identified in human brain [66].…”
Section: Estrogen Receptors In Fetal Lambs 1155supporting
confidence: 83%
“…In addition, AR mRNA expression was found in similar hypothalamic, limbic, and cortical structures as well as in the thalamus and the ventral horn of the spinal cord of adult male and female rats (Simerly et al, 1990). AR mRNA expression was also observed, in the same pattern of distribution, throughout the forebrain of developing male and female rats (McAbee and DonCarlos, 1998). In these studies, the cellular phenotype of AR-expressing cells was not explored.…”
mentioning
confidence: 98%